SEBARAN SPASIAL EKOLOGI NITROGEN DI DANAU TONDANO PROVINSI SULAWESI UTARA - , Sofia Wantasen, Ir.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The Purposes of this study were 1) to study the transformation of Nitrogen into Nitrate, Nitrite, Ammonia and their concentration in inlet, in-lake and outlet of Tondano Lake. 2). To assess the Nitrogen distribution and transformation impacts on abiotic environments (water quality degradation) as well as biotic environments (aquatic plants). 3). To describe the spatial distribution of total nitrogen and its transformation (Nitrate, Nitrite, Ammonia) in Tondano Lake. Location of water quality sample were at the inlet of the lake, in the lake and the outlet of the Lake Tondano. Water quality sample was taken at the inlet of the lake in order to get representation of condition of the rivers, irrigation channel, and drainage housing which flow to the Lake Tondano. The number of samples at the inlet of the Lake Tondano was 25 samples. Total samples from the lake were 29 samples, it was 24 samples from the lake and from the outlet of the lake was five samples. Sampling time from 10 November to 19 Pebruary 2009, rainy season. Water quality sampling done by using composite sampling, lake water brightness with a Disk Seichi Method, and socioeconomic and culture survey carried out by using purposive sampling method. Research variable were Nitrate, Nitrite, Ammonia, pH, water, temperature, DO, turbidity, brightness, and Chlorophyll-a as a biotic parameters. Method of water sampling refered to APHA (2005). Data obtained in this study were analyzed using four-way analysis. The first way was the analysis of laboratory, aimed to determine the physical and chemical properties of water samples at the inlet of the Lake Tondano, Tondano Lake and at the outlet of the Lake Tondano, the second way Nitrogen Mass Balance method. The third way was the statistical analysis using graphs and calculation, and the fourth way was Spatio Ecology Analysis. Results showed that the concentration of nitrogen (Nitrate, Nitrite, Ammonia) at the inlet of the Lake Tondano (input) was very high, while the output was low. This showed that the majority of nutrients left in the lake, causing eutrophication of Lake Tondano. The trophic level of Lake Tondano was Eutrof even lead to hipereutrof. Nitrogen was transformed into nitrate, nitrite, ammonia in inlet, in-lake, and outlet of Tondano Lake. Transformed Nitrogen in inlet of the Lake Tondano was dominated by nitrate. In the lake at the surface, transformed nitrogen was dominated by NH3, while at a depth of five meters was dominated by NO3. Transformation of nitrogen at a depth of 10 meters was dominated by NH3, followed by NO3, NO2. Spatial distribution of total nitrogen could be grouped into 10 class